Disabling barriers—Coping with accessibility of nature in Biosphere Reserves - Klara J. Winkler; Aleksandra Kosanic; Berta Martín‐López (People and Nature, 2025)
Abstract Biosphere Reserves have the mandate to foster the relationship between people and nature, which can benefit people in a variety of ways, including both physical and mental health. With about 16% of the global population, people with disabilities are a significant group of people who, so far, have received limited attention for their needs in research and in discussions about how people relate to nature. We have reviewed accessibility measures in 167 Biosphere Reserves in 18 countries in Europe and North America. We find that accessibility is considered in 58% of cases with at least one measure. However, measures are mainly focused on accessibility for physical disabilities by providing access through infrastructures. We highlight a variety of measures that have been implemented and tested already today in the Biosphere Reserve to serve different needs of a variety of disabilities. In this perspective piece, we aim to illustrate challenges, but also the possibilities that we find to make nature more accessible. Thus, it is necessary to highlight the multi‐dimensionality of disabilities and the need for plural measures to foster just access to protected areas. With this piece, we ultimately aim to start a conversation in the research field of sustainability science that considers a marginalized group that most people will join (temporarily) at some point in their lives: people with disabilities. Read the free Plain Language Summary for this article on the Journal blog.